Multiscale modeling of polymers filled with MWCNTs: the effect of dispersion, waviness, interphase and agglomerations. Issue 9 (13th January 2020) - Polydoropoulou, Panagiota; Tserpes, Konstantinos; Pantelakis, Spiros; Katsiropoulos, Christos
Abstract : Purpose: The purpose of this paper is the development of a multiscale model which simulates the effect of the dispersion, the waviness, the interphase geometry as well as the agglomerations of multi-walled carbon nanotubes (MWCNTs) on the Young's modulus of a polymer filled with 0.4 Vol.% MWCNTs. Design/methodology/approach: For the determination of the homogenized elastic properties of the hybrid material representative unit cells (RUCs) have been used. The predicted homogenized elastic properties were used for the prediction of the Young's modulus of the filled material by simulating a finite element (FE) model of a tensile specimen. Moreover, the model has been validated by comparing the predicted values of the numerical analysis with experimental tensile results. Findings: As the MWCNT agglomerates increase, the results showed a remarkable decrease of the Young's modulus regarding the polymer filled with aligned MWCNTs while only slight differences on the Young's modulus have been found in the case of randomly oriented MWCNTs. This might be attributed to the low concentration of the MWCNTs (0.4 Vol.%) into the polymer. For low MWCNTs concentrations, the interphase seems to have negligible effect on the Young's modulus. Furthermore, as the MWCNTs waviness increases, a remarkable decrease of the Young's modulus of the polymer filled with aligned MWCNTs is observed. In the case that MWCNTs are randomly dispersed into the polymer, both numerical and experimental results have been found to be consistent regarding the Young's modulus. Practical implications: The methodology used can be adopted by any system containing nanofillers. Originality/value: Although several studies on the effect of the MWCNTs distribution on the Young's modulus have been conducted, limited results exist by using a more realistic RUC including a periodic geometry of more than 20 MWCNTs with random orientation and a more realistic waviness of MWCNTs with aspect ratio exceeding 150.